Impact of Chinese, Korean and Japanese Innovation Spillover on Labour Productivity in South African Manufacturing - Mazorodze, Brian Tavonga; Tewari, Devi Datt (Journal of Economics and Behavioral Studies, 2018)
Open economy endogenous growth theories consider physical intermediate imports as a channel through which innovation spreads across international boundaries. We build from this literature and contribute by considering trade in services as the channel through which innovation from China, Korea and Japan influences labour productivity in South Africa’s manufacturing sector between 1995Q1 – 2017Q4. Unlike previous studies, we also compute a composite innovation index using the principal component analysis. Results from the autoregressive distributed lag model are supportive of open economy endogenous growth theories for Japan and Korea. However, for China, the effect is significantly negative adding further concerns over its predatory presence in South Africa.